Common variants in mismatch repair genes and risk of colorectal cancer. Issue 8 (25th March 2008) - Koessler, T; Oestergaard, M Z; Song, H; Tyrer, J; Perkins, B; Dunning, A M; Easton, D F; Pharoah, P D P
Abstract : Background and aim: The mismatch repair (MMR) genes are in charge of maintaining genomic integrity. Mutations in the MMR genes are at the origin of a familial form of colorectal cancer (CRC). This syndrome accounts for only a small proportion of the excess familial risk of CRC. The characteristics of the alleles that account for the remainder of cases are unknown. To assess the putative associations between common variants in MMR genes and CRC, we performed a genetic case–control study using a single-nucleotide polymorphism (SNP) tagging approach. Patients and methods: A total of 2299 cases and 2284 unrelated controls were genotyped for 68 tagging SNPs in seven MMR genes ( MLH1, MLH3, MSH2, MSH3, MSH6, PMS1 and PMS2 ). Genotype frequencies were measured in cases and controls and analysed using univariate analysis. Haplotypes were constructed and analysed using logistic regression. We also carried out a two-locus interaction analysis and a global test analysis. Results: Genotype frequencies were found to be marginally different in cases and controls for MSH3 rs26279 with a rare homozygote OR = 1.31 [95% confidence interval (CI) 1.05 to 1.62], ptrend = 0.04. We found a rare MLH1 (frequency <5%) haplotype, increasing the risk of colorectal cancer: (OR = 9.76; 95% CI, 1.25 to 76.29; p = 0.03). The two-locus interaction analysis has exhibited signs of interaction between SNPs located in genes MSH6 and MSH2 . Global testing has showed no evidence of interaction. Conclusion: It is unlikely that common variants in MMR genes contribute significantly to colorectal cancer.